Nasal function and dysfunction in exercise. Issue 5 (17th February 2016) - Walker, A; Surda, P; Rossiter, M; Little, S
Abstract: Background: There have been recent advances in our appreciation of the functional complementarity of the upper and lower airways. The unified airway begins at the nose: rather than acting merely as a conduit for air to the lungs, the nose and nasal cavity perform an important role in filtering, humidification and immune surveillance. Methods: The physiological and pathological responses of the nasal cavity to exercise and regular training are examined in this narrative review, with specific reference to the relation of nasal health to quality of life, lower airway health and upper respiratory tract infections. Relevant literature is examined and placed in clinical context. Results: There is considerable published evidence to support nasal dysfunction associated with exercise, and a link to lower airway dysfunction. Evidence also supports the role of upper and lower airway dysfunction in the development of upper respiratory tract infection symptoms. Conclusion: Nasal dysfunction in exercise may be a source of considerable morbidity to the regular exerciser, and further research into exercise-induced rhinitis is recommended.